(untitled) (Jurnal Serambi Engineering, 2025)
The high content of sodium (Na) and potassium (K) in biomass materials such as coconut husk can cause fouling and slagging during the combustion process. This study aims to characterize coconut husk briquettes that have been soaked in acetic acid solution to reduce alkali metal content and improve fuel quality. The coconut husk was soaked in 0–4% acetic acid solution for 30–360 minutes, and the best-conditioned husk was then carbonized and pressed into briquettes. The resulting briquettes were tested for calorific value, moisture content, ash content, and residual sodium and potassium levels. The soaking treatment successfully reduced potassium content by 75.78% and sodium by 67.33%; these treated husks were then used as raw material for briquette production. The final briquettes contained 0.5645 mg/g of potassium, 0.0052 mg/g of sodium, a calorific value of 5,535 cal/g, 8.31% moisture content, and 4.59% ash content. These results indicate that soaking coconut husk in acetic acid is an effective pretreatment method to enhance the combustion quality of biomass briquettes by reducing alkali metal content.